2019
DOI: 10.1177/209660831900200105
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Science Communication in Contemporary Canada: A Focus on Anglophone Actors and Networks

Abstract: The landscape of contemporary media presents challenges and opportunities for science writers and communicators. These issues have not yet been fully understood. This paper presents the findings of collaborative work conducted to identify the growth in numbers of social media communicators who are writing about science for the Canadian public. We used emerging media research tools, including Altmetrics, and traditional survey tools. Our goal was to help Canada's professional member associations—Science Writers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(30 reference statements)
2
6
0
Order By: Relevance
“…The gender patterns we observe are also consistent with the literature, with women being predominant in the field ( Riedlinger et al, 2019 ). A feminization trend became visible in the 1980s ( Lewenstein, 2019 ; Pérez-Bustos, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…The gender patterns we observe are also consistent with the literature, with women being predominant in the field ( Riedlinger et al, 2019 ). A feminization trend became visible in the 1980s ( Lewenstein, 2019 ; Pérez-Bustos, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…The psychological strain of being constantly online, exposed on video, and acting responsive to all sorts of comments online also appeared as a challenge in communicating science on YouTube. On Instagram and Twitter, however, Riedlinger et al (2019) have reported a majority of women science communicators, which suggests that maybe the exposition created by the medium is a relevant factor for women who choose to communicate science.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, sociological studies exploring the range of online-active science communicators have included more and more actors. If in earlier times the online communicative activities of scientists, postgraduates and science journalists were the main focus (Bonetta, 2007), today the literature started to contemplate new actors and organizations, such as online citizen science hubs and amateur communicators active in blogs and on social media (Acatech, 2017;Riedlinger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They mentioned that partnerships with male colleagues have helped them reach new audiences. However, on other social media, such as Instagram and Twitter, most science communicators are women (Riedlinger et al, 2019), perhaps indicating that these platforms constitute a better environment for women to communicate science.…”
Section: Women Under Attackmentioning
confidence: 99%